2013
DOI: 10.1016/j.schres.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjunctive intranasal oxytocin on olfactory identification and clinical symptoms in schizophrenia: Results from a randomized double blind placebo controlled pilot study

Abstract: Background Deficits in olfactory identification have been widely reported in patients with schizophrenia (SZ) and are associated with negative symptomatology. Adjunctive oxytocin delivered intranasally has been shown to improve some aspects of social cognition as well as positive and negative symptoms in patients with schizophrenia. Given the intranasal delivery route of oxytocin to olfactory pathways and that olfactory abnormalities are a potential endophenotype in SZ, we investigated the effect of intranasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 58 publications
2
82
0
Order By: Relevance
“…Our findings extend those of other studies (Lee et al, 2013), and suggest that the oxytocin system plays a role in some aspects of the olfactory deficits in schizophrenia. However, oxytocin did not improve participants' ability to detect anise, suggesting some specificity to its olfaction-enhancing effect.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings extend those of other studies (Lee et al, 2013), and suggest that the oxytocin system plays a role in some aspects of the olfactory deficits in schizophrenia. However, oxytocin did not improve participants' ability to detect anise, suggesting some specificity to its olfaction-enhancing effect.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, there is growing evidence that oxytocin administration to patients with schizophrenia improves emotion recognition and higher-level social cognition and decreases both positive and negative symptoms (Gumley et al, 2014). Additionally, a recent study that administered 20 IU of oxytocin or placebo twice daily for three weeks to patients with schizophrenia found that oxytocin improved patients' ability to identify pleasant, but not neutral or unpleasant odors (Lee et al, 2013). Taken together, this evidence suggests that oxytocin administration may reduce olfactory deficits in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only 1 meta-analysis of oxytocin for the treatment of schizophrenia has been reported [15]. The previous meta-analysis included four RCTs [8,20,27,31] that evaluated the psychopathology and found that total symptoms, positive symptoms, and negative symptoms improved significantly in the oxytocin group; however, the Positive and Negative Syndrome Scale (PANSS) [18] general subscale scores did not improve in comparison with the placebo group (Table 1). However, seven RCTs with oxytocin have been conducted for the treatment of schizophrenia to date [5,7,8,12,20,27,31].…”
Section: Introductionmentioning
confidence: 99%
“…Both the animal and human literature has linked oxytocin and vasopressin with social affiliative and agonistic behavior, 41 and intranasal oxytocin administration has been shown to improve negative symptoms in schizophrenia patients. 42 The present study demonstrates that, in general, male mutants were more affected than females by mutation of NRG1, DISC1 or NRG1 × DISC1. Sexually dimorphic effects in genetic mouse models of psychosis are commonly observed.…”
Section: Effects Of Co-disruption Of Neuregulin-1 × Disc1mentioning
confidence: 48%